2022
DOI: 10.2337/dc22-0579
|View full text |Cite
|
Sign up to set email alerts
|

Comparing IADPSG and NICE Diagnostic Criteria for GDM in Predicting Adverse Pregnancy Outcomes

Abstract: OBJECTIVE To compare the performance of diagnostic criteria for gestational diabetes mellitus (GDM) proposed by the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) with those endorsed by the National Institute for Health and Care Excellence (NICE) in predicting adverse pregnancy outcomes. RESEARCH DESIGN AND METHODS We performed a secondary data analysis of the Hyperglycemia and Adverse Pregnancy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The reason for the discrepancy may be explained by the different ethnicities of the participants, variations in study design, time points of SF concentration measurement, diagnostic criteria, and other confounding factors. 18,31,34,35 In their study, iron deficiency (ferritin < 12 ug/L) accounted for 52% of the total population, 31 compared with only 12% in our cohort. Moreover, the time points of SF concentration measurement were also later than ours.…”
Section: Discussionmentioning
confidence: 46%
“…The reason for the discrepancy may be explained by the different ethnicities of the participants, variations in study design, time points of SF concentration measurement, diagnostic criteria, and other confounding factors. 18,31,34,35 In their study, iron deficiency (ferritin < 12 ug/L) accounted for 52% of the total population, 31 compared with only 12% in our cohort. Moreover, the time points of SF concentration measurement were also later than ours.…”
Section: Discussionmentioning
confidence: 46%
“…Since there were 2 subjects with high FBG levels only at T2 who were included in both the ENG and LNG groups, we did not perform any comparison analysis between the two groups. According to the diagnostic criteria for GD proposed by the International Association of the Diabetes and Pregnancy Study Groups (IADPSG) [ 22 ], all those women in the ENG, LNG and WHG groups had GD. Based on differences in serum lipid levels, the subjects were assigned into the following 3 groups: ① dyslipidemia starting from T1 of pregnancy (DL1, n = 6), ② dyslipidemia since T2 (DL2, n = 16) and ③ dyslipidemia only in T3 (DL3, n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…Pregnant women with lower maternal age are less likely to suffer from severe dysglycemia; thus, interventions might be more effective and insulin resistance might be easier to improve in this subgroup [ 53 ]. All non-western country studies used ADA guidelines as diagnostic criteria, suggesting a disagreement of diagnostic criteria as a previous study found IADPSG (i.e., ADA) criteria more favorable than NICE for identification of adverse pregnancy outcomes among Asian and Hispanic women, while they are comparable to NICE among White women [ 57 ]. Furthermore, studies with lower glucose thresholds for GDM selection may have less impact.…”
Section: Discussionmentioning
confidence: 99%